Climate litigation and justice in Africa - Bouwer, Kim; Etemire, Uzuazo; Field, Tracy-Lynn; Oluborode Jegede, Ademola (Bristol University Press, 2024)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. In recent years, climate litigation has become an important subject of global scholarly and policy interest. However, developments within the Global South, particularly in Africa, have been largely neglected. This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation. Spanning a range of approaches and jurisdictions, the book challenges universal concepts around climate and the role of activism (including litigation) in seeking to advance climate governance.